Peran Intellectual Capital dalam Memoderasi Pengaruh GCG dan Manajemen Laba terhadap Financial Distress - Wicaksono Abdinur Muhamad; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Bankruptcy is something that is closely related to the business world. This research aims to prove the alleged influence of Good Corporate Governance (GCG) and Profit Management on Financial Distress with Intellectual Capital as a moderating variable. The population in this research is all State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (BEI). The sample for this research was 70 companies during 2019-2023 using the proportional sampling method. This research uses a multiple regression analysis method using E-Views 10. The research results show that GCG, namely independen commissioners, audit committees and earnings management have a significant effect on financial distress. This is because the role of independen commissioners and an effective audit committee as supervisors of management in carrying out company activities that can be detrimental to the company can be avoided, and can prevent opportunistic actions and behaving selfishly to achieve its own goals and earnings management is proven to be able to increase the company's fraud so that the company went bankrupt.